2013
DOI: 10.1152/ajplung.00354.2012
|View full text |Cite
|
Sign up to set email alerts
|

Distinct responses of protein turnover regulatory pathways in hypoxia- and semistarvation-induced muscle atrophy

Abstract: de Theije CC, Langen RC, Lamers WH, Schols AM, Köhler SE. Distinct responses of protein turnover regulatory pathways in hypoxia-and semistarvation-induced muscle atrophy. Am J Physiol Lung Cell Mol Physiol 305: L82-L91, 2013. First published April 26, 2013 doi:10.1152/ajplung.00354.2012.-The balance of muscle protein synthesis and degradation determines skeletal muscle mass. We hypothesized that hypoxia-induced muscle atrophy and alterations in the regulation of muscle protein turnover include a hypoxia-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 57 publications
5
38
0
Order By: Relevance
“…Some works reported an increase in MAFbx mRNA [74,119], while this expression in not always observed after prolonged exposure [101,123]. The other well studied E3 ligase MuRF1 presents a similar expression pattern with an increase during the first week of hypoxia exposure [74,123] and a return to basal level during longer exposure [101,123]. These patterns of MuRF1 and MAFbx expression in response to hypoxia are similar to those reported during unloading and muscle inactivity [129].…”
Section: Hypoxia-related Regulation Of Proteolytic Systemssupporting
confidence: 75%
See 4 more Smart Citations
“…Some works reported an increase in MAFbx mRNA [74,119], while this expression in not always observed after prolonged exposure [101,123]. The other well studied E3 ligase MuRF1 presents a similar expression pattern with an increase during the first week of hypoxia exposure [74,123] and a return to basal level during longer exposure [101,123]. These patterns of MuRF1 and MAFbx expression in response to hypoxia are similar to those reported during unloading and muscle inactivity [129].…”
Section: Hypoxia-related Regulation Of Proteolytic Systemssupporting
confidence: 75%
“…While this negative influence was thought to be primarily related to cold exposure, high energy expenditure and especially hypophagia [99], we and others have demonstrated that hypoxia per se accounts for skeletal muscle atrophy [74,100,101]. Although numerous differences exist between studies (altitude level, normobaric vs. hypobaric hypoxia, exposure duration, age of animals and acclimatization duration), analysis of published data clearly shows a significant positive correlation between hypoxia severity and the level of muscle atrophy in rats (Fig.…”
Section: Regulation Of Muscle Mass Structural Modificationsmentioning
confidence: 61%
See 3 more Smart Citations